The Turnpike Theorem of Morishima - McKenzie, Lionel W. (Review of Economic Studies, 1963)
The Turnpike Theorem of Morishima Get access Lionel W. McKenzie Lionel W. McKenzie Rochester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 3, October 1963, Pages 169–176, https://doi.org/10.2307/2296317 Published: 01 October 1963